(untitled) (International Journal of Physiotherapy, 2019)
Background: Dysmenorrhea or pain during menstruation is commonly seen in young women and largely impacts their quality of life. Pain medications are largely used to tackle this situation; however, they have side effects with regular use. Safe, effective pain-relieving modalities are crucial to help women cope with this situation. There is extensive literature proving the effectiveness of TENS for relieving the pain in primary dysmenorrhea; however, literature proving the same for IFT is sparse. Thus this research aims to investigate and compare the effectiveness of both the modalities in primary dysmenorrhea. Methods: 30 samples(17-25) were included in this study. Using the Simple Random Sampling method, the subjects were divided into two groups. One group received therapy through TENS(80-120 Hz, 20mins, Intensity as per tolerance) and the other through IFT(4PV,80-150HZ, 20 mins, Intensity as per tolerance). Electrical stimulation was given in the region of maximal pain. The Intensity of pain before and after treatment was recorded using the Numerical Pain Scale. The duration of pain relief and the need for analgesic post the therapy was also noted. Results: TENS and IFT are both extremely effective for the relief of pain in primary dysmenorrhea (P<0.0001). There is no significant difference in their effect on the comparison (P=0.422). And most of the subjects in both groups did not need analgesics after therapy. Conclusion: Both TENS and IFT are equally effective in the relief of pain in primary dysmenorrhea. However, tolerance to IFT currents is better among young women as they are medium frequency currents.